Competence Quality Improvement through Professional Training and Education - Karsono, Budi (Perhimpunan Sarjana Ekonomi dan Bisnis, 2023)
Quality shows ability and reliability in carrying out tasks, especially in the security sector work unit. Quality indicators are a must, because in carrying out the task of maintaining security there is a risk of loss of life or the integrity of the country. This study aims to see the effect of professional training and education on improving the quality of competence of Indonesian soldiers. To show that there is influence, a quantitative research method is used on the basis of data disclosure. A total of 80 marines from the headquarters of the Indonesian National Armed Forces who became research correspondents. Data analysis using statistical regression test. Research data was collected through a purposive method by distributing questionnaires. The results of the study show that there is a strong allegation that the quality of competence increases significantly if soldiers receive professional and educational training programs. This means that the quality of soldier competence needs to be strengthened both in terms of technical ability and knowledge, so that soldiers have a comprehensive level of combat intelligence, encompassing technical intelligence, intellectual intelligence and mental maturity.